2009
DOI: 10.2298/vsp0905377k
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of difficult intubation in 2 000 patients undergoing thyroid surgery: A single center experience

Abstract: The incidence of DI was higest in patients with polynodal goiter but extremly DI was present mostly in patients with hyperthiroidism. Men seem to be at higher risk for DI than women. Scoring system used in this study for prediction of DI may be useful in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Although both study groups included more females, DI was significantly more prevalent in men, which is consistent with the results of our previous study 10 . Results reported by Bouaggad et al 5 are in accordance with our results.…”
Section: Nevena Kalezić Et Alsupporting
confidence: 91%
See 1 more Smart Citation
“…Although both study groups included more females, DI was significantly more prevalent in men, which is consistent with the results of our previous study 10 . Results reported by Bouaggad et al 5 are in accordance with our results.…”
Section: Nevena Kalezić Et Alsupporting
confidence: 91%
“…The incidence of DI was 6.81%. In our previous study 10 on 2000 patients undergoing thyroid surgery, the incidence was 5.5%. A similar incidence (5.3%) was demonstrated in a study by Bouaggad et al 5 .…”
Section: Discussionmentioning
confidence: 93%
“…However, they found an increased incidence of difficult intubation when malignant thyroid was present. Although there is a claim that big goitres are associated difficult airway [15] based on the assumption that, big goitres dislocate the trachea. Our conclusion is in line with that of Bouaggad et al in that presence of big goitres is not always associated with deformity leading to difficult airway.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that DI was highest in patients with polynodal goiter but extreme DI was present mostly in patients with hyperthyroidism and men seem to be at higher risk for DI than women [15].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation